KUALITAS PELAYANAN PUBLIK DALAM MENINGKATKAN KEPUASAN PELANGGAN AIR BERSIH DI KANTOR PERUSAHAAN UMUM DAERAH AIR MINUM (PERUMDAM) TIRTA TAKAWA KABUPATEN BUTON - , Nelvianti; La Asiri; Mastia (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
Regional Drinking Water Company (PDAM) is a company owned by the regional government which is tasked with managing raw water into drinking water. Regional governments have the authority to regulate drinking water management. PDAM is also an agency that often receives quality service complaints from the public as its clients. The aim of this research is to describe/know the extent of the level of public services provided by PERUMDAM Tirta Takawa, Buton Regency to increase customer satisfaction. This research uses the dimensions of service quality, namely Tangibles, Reliability, Responsiveness, assurance and empathy. This research uses a qualitative method with a descriptive approach, in the sampling technique using purposive sampling with the main informant coming from PERUMDAM Tirta Takawa customers, Buton Regency and the supporting informants being employees from PERUMDAM Tirta Takawa, Buton Regency. Ways to collect data include observations, interviews, and documentation studies. This research found that the services provided by staff at the Tirta Takawa Regional Drinking Water Company Office (PERUMDAM), Buton Regency were satisfactory, including in terms of employees’ ability to provide clear information, responsibility in completing tasks, and responsiveness in handling community problems during service.